Molecular mechanisms and biomarkers of autophagy in early onset preeclampsia: Key genes, pathways, and potential diagnostic/therapeutic targets - Kusuma, Anak Agung Ngurah Jaya (Universitas Airlangga, 2025)
HIGHLIGHTS Dysregulated autophagy in trophoblasts contributes to abnormal placentation and impaired spiral artery remodeling in early-onset preeclampsia. Oxidative stress and excessive mitochondrial ROS disrupt the autophagic balance, leading to cellular dysfunction and placental ischemia. Key autophagy-related genes (e.g., BECN1, LC3, ATG5, mTOR, TFEB) may serve as diagnostic or therapeutic targets in early-onset PE. Understanding the autophagy–oxidative stress interaction could inform biomarker development and novel interventions. ABSTRACT The pathogenesis of preeclampsia (PE) remains incompletely understood, with multiple mechanisms proposed. Among these, dysregulation of autophagy has emerged as a critical factor. Autophagy is essential for implantation, placental development, and pregnancy maintenance. Extravillous trophoblasts (EVTs) invade the decidua and proximal myometrium under hypoxic conditions, and autophagy supports this invasive process. In PE, impaired placentation has been associated with abnormal autophagic activity in trophoblastic cells. Furthermore, oxidative stress and excessive mitochondrial reactive oxygen species (ROS) production contribute to the pathophysiology of PE, potentially driving both insufficient and maladaptive upregulation of autophagy depending on the cellular microenvironment. Thus, PE is characterized not by a uniform increase or inhibition, but rather by disrupted autophagic balance. This review aims to clarify the role of autophagy dysregulation in the pathogenesis of PE.